OptiWeb: An Optimization Application for Steel Cutting Industries Ported to the Grid in the Framework of PireGrid Project - Ibar, Jaime; Ruiz, Gonzalo; Valles, Ruben; Tarancón, Alfonso (Computing and Informatics, 2012)
PireGrid citepiregrid (Project Number EFA35/08) is an INTERREG IV A project which has two main objectives, namely the deployment of a production Grid Computing infrastructure in the regions of Aragon, Aquitaine and Midi-Pyrenees and the achievement of successful cases in execution of applications from small and medium size companies of the named regions, in order to demonstrate its usage of these emerging technologies to the companies. In the framework of this project we present Optiweb, which is the first successful porting of an application from Schnell Software [2], and the process followed to adapt it to a web interface and its transparent execution in a gLite grid infrastructure.